THE INFLUENCE OF BRAND EQUITY, PRODUCT QUALITY AND PRICE ON FORMAL CARDINAL PRODUCT PURCHASE DECISIONS AT PT. SUN DEPARTMENT STORE MEDAN MALL - Yusnandar, Willy; Habib, Muhammad (Proceeding International Seminar of Islamic Studies, 2024)
The aim of this research is to determine and analyze the influence of brand equity, product quality and price on purchasing decisions both partially and simultaneously. The approach used in this research is an associative approach. The population in this study were all people who purchased Cardinal Formal products at PT. Matahari Department Store Medan Mall . The sample in this study using the Lemeslow formula was 96 people who purchased Cardinal Formal products at PT. Matahari Department Store Medan Mall . Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS ( Statistical Package for the Social Sciences ) software program version 24.00. The results of this research prove that partially and simultaneously brand equity, product quality and price have a significant effect on purchasing decisions for Cardinal Formal products at PT. Matahari Department Store Medan Mall